BASKET-PROVE II: BP-DES Noninferior to DP-DES - Hoyle, Brian (MD Conference Express, 2014)
This article discusses the main results of the randomized BASKET Prospective Validation Examination II trial [BASKET-PROVE II], which compared the long-term outcome of biodegradable-polymer drug-eluting stents to both durable-polymer drug-eluting stents and bare metal stents.